Reframing Conflict Management in Primary Schools: A Social Justice Perspective on Strategies for Addressing Conflict between School Management Teams and Teachers - Prudence Mevas Baloyi; Siyanda Mluleki Kenneth Cele (International Journal of Educational Innovation and Research, 2026)
Conflict between School Management Teams (SMTs) and teachers remains a persistent challenge in primary schools, yet limited research has examined how such conflict is experienced and managed collectively within specific socio-contextual settings. Guided by Nancy Fraser's three-dimensional theory of social justice, particularly the principles of redistribution, recognition, and representation, this qualitative study investigated the nature of conflict between SMTs and teachers and explored conflict management strategies that promote equity, inclusion, and democratic participation. The study was conducted in two primary schools in the Ekurhuleni South District of Gauteng Province, South Africa. An interpretivist paradigm informed the research, and data were generated through semi-structured interviews with five purposively selected participants, comprising a principal, deputy principal, departmental head, and teachers. Thematic analysis revealed that conflict was primarily associated with communication breakdowns, unequal power relations, inconsistent leadership practices, and limited participatory decision-making. Interpreted through a social justice lens, the findings demonstrate that effective conflict management extends beyond procedural resolution to recognising teachers' professional voices, promoting equitable distribution of responsibilities, and strengthening inclusive leadership practices. Although the findings are limited to a small sample from a single district and are therefore not intended to be statistically generalisable, they provide valuable contextual insights into conflict management in South African primary schools. The study recommends targeted professional development and policy initiatives that strengthen socially just leadership practices, promote participatory school governance, and enhance collaborative relationships between SMTs and teachers.